Robosoldiers : thank you for your servos : an anthology - Lawson, Stephen, 1980- (Baen, 2023)
"The future of cybernetic warfare: Robosoldiers. They take many forms, from disembodied AI to humanlike androids and more. But at their cores beat the cybernetic hearts of warriors! In these stories of hard military SF, you will journey to the battlefields of tomorrow with the veterans who have been there and the researchers developing the next phase of battle and get a glimpse into the future of warfare. Contributors: M.T. Reiten, Martin L. Shoemaker, Doug Beason, Richard Fox, Sean Patrick Hazlett, Monalisa Foster, Phillip Pournelle, Weston Ochse, David Drake, T.C. McCarthy, Brad R. Torgersen, Stephen Lawson, and Philip Kramer"--